Astrocyte-Derived Thrombospondin Induces Cortical Synaptogenesis in a Sex-Specific Manner - Mazur, Anna (eNeuro, 2021)
The regulation of synaptic connectivity in the brain is vital to proper functioning and development of the CNS. Formation of neural networks in the CNS has been shown to be heavily influenced by astrocytes, which secrete factors, including thrombospondin (TSP) family proteins, that promote synaptogenesis. However, whether this process is different between males and females has not been thoroughly investigated. In this study, we found that cortical neurons purified from newborn male rats showed a significantly more robust synaptogenic response compared with female-derived cells when exposed to factors secreted from astrocytes. This difference was driven largely by the neuronal response to TSP2, which increased synapses in male neurons while showing no effect on female neurons. Blockade of endogenous 17β-estradiol (E2) production with letrozole normalized the TSP response between male and female cells, indicating a level of regulation by estrogen signaling. Our results suggest that male and female neurons show a divergent response to TSP synaptogenic signaling, contributing to sex differences in astrocyte-mediated synaptic connectivity.